2018
DOI: 10.1111/jpc.14142
|View full text |Cite
|
Sign up to set email alerts
|

‘I think we've had a health screen’: New offshore screening, new refugee health guidelines, new Syrian and Iraqi cohorts: Recommendations, reality, results and review

Abstract: There are substantial challenges with the current primary care screening model in Victoria. Disability, developmental and mental health concerns were prominent in this cohort, and many children had delays in education access, compounding prior disadvantage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1
12

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 12 publications
0
7
1
12
Order By: Relevance
“…This difference is likely because permanent applicants were only screened if they were from a high-burden setting, and the humanitarian intake at the time was predominantly from countries with relatively low TB prevalence (largely refugee applicants from Syria and Iraq) ( 28 ). Nevertheless, the proportion of positivity (2.1%) in humanitarian applicants was lower than previous LTBI prevalence estimates in refugee-background children tested in Australia, including from the Middle East ( 11 , 29 ).…”
Section: Discussioncontrasting
confidence: 72%
“…This difference is likely because permanent applicants were only screened if they were from a high-burden setting, and the humanitarian intake at the time was predominantly from countries with relatively low TB prevalence (largely refugee applicants from Syria and Iraq) ( 28 ). Nevertheless, the proportion of positivity (2.1%) in humanitarian applicants was lower than previous LTBI prevalence estimates in refugee-background children tested in Australia, including from the Middle East ( 11 , 29 ).…”
Section: Discussioncontrasting
confidence: 72%
“…Despite the existence of country-level guidance for pre-migration mental health screening (for example, from the USA [ 109 ], Australia [ 61 ], or New Zealand [ 110 ]), there are very few published reports evaluating these processes. The published literature shows that most assessments occur post-arrival to the resettlement state.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies noted the difficulty of following up with refugees as they often get transferred from one location to another in the first few months post-arrival [ 89 , 94 ]. Further, one Australian study reported challenges with the information transfer between and within pre-migration and post-arrival health systems, causing duplication of avoidable tests, increased costs, inefficiencies, and possible clinical consequences [ 61 ]. Evidence from the UK also identified critical operational issues with the information flow and supports the notion that further evaluation of pre-departure screening is warranted prior to widespread implementation [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific cohort vulnerability is described including physical, educational and mental health issues, with specialist health care recommended on resettlement. [1][2][3] Aim: We aim to describe the demographic and clinical profiles of recently arrived Syrian and Iraqi refugees across health domains: physical, psychosocial, developmental and educational. We predicted manifestation of earlier psychological symptoms related to direct warfare exposure compared to previous humanitarian RHS cohorts.…”
mentioning
confidence: 99%